Cholelithiasis and chronic cholecystitis in a ten-year-old-boy: a case report - Carissa Lidia; I Gusti Ngurah Sanjaya Putra; I Putu Gede Karyana; Ni Nyoman Metriani Nesa; I Made Darmajaya; Kadek Deddy Ariyanta (Intisari Sains Medis, 2020)
Background: Cholelithiasis in children is uncommon and challenging to diagnose because the patient is often asymptomatic and the clinical feature doesn't clearly depict cholelithiasis or cholecystitis. This case study aims to describe a rare case of cholelithiasis with chronic cholecystitis in a ten-year-old boy.Case Presentation: A ten-year-old boy presented with umbilical pain, nausea, and emesis. Physical examination showed there is no tenderness in all abdominal quadrants with a negative Murphy sign. Laboratory results revealed elevated white blood cell count 20.42x103/?L, elevated erythrocyte sedimentation rate 47.2 mm/hour, normal liver function tests, urine, and stool analysis. He underwent transabdominal ultrasound twice. The latest transabdominal ultrasound showed cholelithiasis, free fluid around the pelvic region due to suspected visceral organ perforation. Laparoscopic cholecystectomy was performed without complication. The result of pathology anatomy examination was chronic cholecystitis. The patient was discharged 3 days after surgery in good condition. The long-term prognosis of the patient was good.Conclusion: Even though the patient is male with good nutritional status (not obese), the patient was in the mean age that was identified as a key contributor to this disease. Ultrasonography examination is a screening modality that is still an excellent diagnostic tool with 95% accuracy even though it is highly operator dependent. Laparoscopic cholecystectomy is a gold standard for management even in children with decreased pain and shorter lengths of stay in the hospital.